Profil pengembangan literasi budaya dalam pembelajaran ilmu pengetahuan alam dan sosial (IPAS) di kelas V sekolah dasar - Roosyida Firdaus Andhini; Karsono Karsono; Peduk Rintayati (Didaktika Dwija Indria, 2025)
This study aims to describe the cultural literacy development profile of the cultural literacy development profile in science science learning in grade 5 SD N 2 Drono in 2023/2024. This study uses a qualitative method with a phenomenological approach. The subjects in this study are class teachers and 7 students of grade V of SD Negeri Drono 2 Klaten. The research data was obtained through observation techniques, interviews and document studies. To test the validity of the data, this study uses source triangulation and time triangulation. The researcher used an interactive model data analysis technique developed by Miles and Huberman. The teacher has integrated cross-cultural awareness into the planning, implementation, and evaluation of IPAS lessons. Various media, learning resources, and teaching methods are used to help students understand cultural differences. The research indicates that the teacher has fostered an inclusive environment that embraces cultural diversity. The teaching modules have comprehensively developed cross-cultural awareness. IPAS learning activities have enhanced cultural literacy, particularly in cross-cultural awareness. The teacher also evaluates IPAS learning by incorporating cross-cultural aspects. This promotes students' understanding and appreciation of local and diverse cultures, which is essential for effective interaction in heterogeneous communities.